Socially Responsible Investment, Internal Financing Sources and Access to Bank Financing: Evidence from Indian Survey Data - Amarjit Gill; Harvinder S. Mand; Afshin Amiraslany; Neil Mathur (Asian Academy of Management Journal of Accounting and Finance, 2017)
We investigated the association between socially responsible investment, internal financing sources, and access to bank financing in the production industry of India. Using a survey research design, owners of small production firms were asked about their perceptions regarding socially responsible investment, internal financing sources, and access to bank financing. We found that socially responsible investment and internal financing sources help owners of small production firms improve access to bank financing. This study contributes to the literature on the relationship between socially responsible investment, internal financing sources, and access to bank financing. The findings may be useful for financial managers, production firm owners, investors, consultants, and other stakeholders.